APLIKASI SISTEM INFORMASI AKUNTANSI JASA PENYEWAAN KAPAL BERBASIS WEB PADA PT SEKUMBANG PERMATA ENGINEERING - Rosiska, Evan; Nopiana, Puspita Rama (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
PT Sekumbang Permata Engineering is a boat rental companies, where the numberof boats that are rented by 4 units ferry for passenger transport. The vessels areleased by the company is owned by the company and in collaboration with severalparties outside the company. Boat rental process currently takes a long timebecause their price negotiation, contracting and leasing invoice. Contracts that havebeen approved are sent via email or other delivery service to be signed by theconsumer. The method used in designing applications Accounting InformationSystems (SIA) vessel charter services, web-based approach with a waterfall SDLCand MySq web programming language. Conclusion the results of the study are (1)the application system is expected to assist the company in finding rentalinformation, anywhere and anytime. (2) to provide a solution of the notificationscharter vessel that will mature and improve archival data storage.